2022
DOI: 10.1186/s13034-022-00468-9
|View full text |Cite
|
Sign up to set email alerts
|

Weight spectrum and executive function in adolescents: the moderating role of negative emotions

Abstract: Background While recent works suggested that overweight/obesity may impair executive function (EF), the overweight/obesity-EF relationship has not been well studied in adolescents. Furthermore, no research has investigated adolescent EF impairments across the weight spectrum (e.g., underweight or thinness, normal, overweight/obesity), especially those with underweight condition, with the moderating effect of negative emotions in the weight-EF association being limitedly investigated. We aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This study was conducted in Shangrao (December 2018), a relatively socioeconomically underdeveloped city located in downstream Yangtze River in southeast China. The multistage cluster random sampling method we used was reported in prior study 20. Briefly, based on the per capita disposable income of Chinese residents in 2016, four districts/counties were selected, and four schools (two lower secondary and two upper secondary) stratified by rural and urban areas were randomly chosen from each district/county, then one class from each grade in the sampled 16 schools was randomly selected, and finally, all students in the selected classes were invited to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted in Shangrao (December 2018), a relatively socioeconomically underdeveloped city located in downstream Yangtze River in southeast China. The multistage cluster random sampling method we used was reported in prior study 20. Briefly, based on the per capita disposable income of Chinese residents in 2016, four districts/counties were selected, and four schools (two lower secondary and two upper secondary) stratified by rural and urban areas were randomly chosen from each district/county, then one class from each grade in the sampled 16 schools was randomly selected, and finally, all students in the selected classes were invited to participate in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Two data acquisition schemes, an online questionnaire survey, and offline accelerometer wearing, were performed simultaneously to collect adolescents' sociodemographic information, lifestyle behaviors, physical and mental health outcomes. Details of the protocol can be found in one prior published study [63]. This study was approved by the Human Ethics Committee of the Shanghai Children's Medical Center according to the Declaration of Helsinki (SCMCIRB-K2018103).…”
Section: The Adolescent Datasetmentioning
confidence: 99%
“…The BRIEF has 86 items, each one is rated on a three-point Likert-type scale, including never, sometimes and often, and parents of the participants were asked to select the most suitable answer for their adolescents in the past 6 months. After cleaning the raw data [63], three indexes were calculated: 1) the BRI, represents the ability to modulate behavioral and emotional responses appropriately; 2) the MI, evaluates the ability to solve problems, including initiating activities and tasks, holding information in mind for purpose of completing a task, anticipating future events, monitoring the effects of one's behaviors on others and keeping track of daily assignments; 3) the GEC, is a composite measure of all the cognitive functions mentioned above. Values of BRIEF scores reflect the extent of impairment of the corresponding cognitive functions, and higher scores indicate greater impairments.…”
Section: Measurement Of Cognitive Functionsmentioning
confidence: 99%
“…Nevertheless, this study used only the BMI indicator, which was less sensitive to reflect body fat distribution, whereas waist to height ratio (WHtR) may serve as a more significant marker of abdominal obesity or visceral fat than BMI [11, 12]. Cross‐sectional observations have suggested that WHtR might be more sensitive than BMI in examining the associations of adolescent obesity with impairments in executive function [13] and psychological well‐being [14], as abdominal obesity might be more likely to induce structural brain changes by activating inflammation in adipose tissue [13]. Therefore, studies elucidating the impacts of different BMI and WHtR developmental trajectories on adolescent mental well‐being are warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional observations have suggested that WHtR might be more sensitive than BMI in examining the associations of adolescent obesity with impairments in executive function [13] and psychological wellbeing [14], as abdominal obesity might be more likely to induce structural brain changes by activating inflammation in adipose tissue [13]. Therefore, studies elucidating the impacts of different BMI and WHtR developmental trajectories on adolescent mental well-being are warranted.…”
Section: Introductionmentioning
confidence: 99%